The impact of intermediary remuneration in differentiated insurance markets - Annette Hofmann; Martin Nell (Hamburg University, Institute for Risk and Insurance, 2008)
This article deals with the impact of intermediaries on insurance market transparency and performance. In a market exhibiting product differentiation and coexistence of perfectly and imperfectly informed consumers, competition among insurers leads to non-existence of a pure-strategy market equilibrium. Consumers may become informed about product suitability by consulting an intermediary. We explicitly model two intermediary remuneration systems: commissions and fees. We find that social welfare under fees is first-best efficient but fees lead to lower expected profits of insurers and non-existence of a pure-strategy market equilibrium. Commissions, in contrast, cause 'overinformation' of consumers relative to minimal social cost, but yield a full-information equilibrium in pure strategies associated with higher expected profits of insurers. This might explain why intermediaries are generally compensated by insurers.
Keywords: D43; G22; L13; 330; product differentiation; intermediation; insurance oligopoly